Facilities and Equipment Service Management Model: Team Motivation Practices - Romana, Fernando Acabado; Gestoso, Carlos Guillen; Fernandez, Silvia Gonzalez; Forero, Antónia Ávila (Archives of Business Research, 2024)
This study aims to deepen knowledge of hospital service management, with a focus on functions, procedures and processes related to non-medical Facilities and Equipment. Using four interviews with key professionals and a questionnaire completed by 52 employees, the research explores common themes and their practical implications. The study offers a comprehensive analysis of hospital dynamics, highlighting the complexity of functions and procedures for operational efficiency. It identifies effective process monitoring as crucial to the timely completion of hospital activities and proposes areas for improvement, such as process management and digitalisation, providing valuable guidance for managers and healthcare professionals.